Barriers and supports in engineering career development: An exploration of first-year students - Ramos-Sandoval R. (2020)
Previous research has found that first-years in college is challenging due to changes in academic demands and the adaptation process. In addition to this, research on career development has found that barriers and supports may influence career interest, motivation to continue and student retention. This study explores the influence of specific supports and barriers among first-year engineering college students. To reach this goal, a case study was conducted with 425 engineering students at three universities in Lima, Peru. Based on Social Cognitive Career Theory (SCCT), we performed a Structural Equation Model (SEM) to assess effects of contextual factors such as barriers and supports on self-efficacy, coping self-efficacy, and goals. Results showed that certain supports and barriers influence self-efficacy, cope self-efficacy and goals. Effects of these factors in first-year students and possible strategies for retention in STEM careers are discussed. © 2020 ASTES Publishers. All rights reserved.